Thin Media Images Decrease Women’s Body Satisfaction: Comparisons Between Veiled Muslim Women, Christian Women and Atheist Women Regarding Trait and State Body Image - Wilhelm, Leonie; Hartmann, Andrea S.; Becker, Julia C.; Kisi, Melahat; Waldorf, Manuel; Vocks, Silja (Frontiers in Psychology, 2019)
Research in diverse populations has often found that thin media images negatively affect women’s state body image, with many women reporting lower body satisfaction after exposure to pictures of thin models than before exposure. However, there is evidence that theistic affirmations might buffer against the negative effect of media on body image. Furthermore, based on cross-sectional and correlation analyses, religiosity and the Islamic body covering are discussed as protective factors against a negative trait body image. However, there is no experimental research on veiled Muslim women’s state body image. Therefore, the current study experimentally investigated whether the body satisfaction of veiled Muslim women (n = 66) decreased after exposure to thin media images compared to pictures of furniture as a control condition. Christian women (n = 90) and atheist women (n = 74) were included as control groups, and participants were randomly assigned to the two conditions. Prior to the experimental session, participants’ trait body image was assessed using an online questionnaire comprising questions about body satisfaction, thin-ideal internalization, pressure to be thin, and physical appearance comparisons. The results showed that body satisfaction decreased in the experimental condition and not in the control condition, but no significant differences in pre-post changes were found between the three groups. However, in the experimental condition, veiled Muslim women reported a more positive state body image than did Christian women. Moreover, veiled Muslim women had a more positive trait body image than did Christian women and atheist women. Thus, veiled Muslim women reported lower levels of thin-ideal internalization, pressure to be thin, and physical appearance comparisons than did Christian women and atheist women. As the pre-post changes in body satisfaction did not differ between the three groups, veiling might not buffer against the negative effect of thin media images on state body image. Nevertheless, given the more positive trait body image of veiled Muslim women compared to Christian and atheist women, veiling might positively influence body image in the longer term.